Influência de bráquetes e tipos de ligadura no acúmulo microbiano e na desmineralização do esmalte adjacente a dispositivos ortodônticos - Pacce, Marcos Antonio (2011)
The orthodontic treatment has been related to caries lesions development, since the devices used are biofilm retentive. This thesis aimed to evaluate the effect of ligation type and type of orthodontic bracket in the mineral loss and biofilm accumulation to these devices. To accomplish this goal, three studies were conducted. The first study consisted in a systematic literature review, where electronic databases (PubMed, Embase, Cochrane Central Register of Controlled Trials, ISI Web of Knowledge, TRIP, Scopus, and SciELO) were searched up to July 2011. Clinical trials or in situ studies that assessed the effect of types of brackets or ligatures on biofilm accumulation and/or enamel demineralization were selected. Non-controlled studies, in vitro studies, or studies not reporting on the established outcomes were excluded. The second study assessed the enamel demineralization around six types of brackets/archwire ligation combinations. In that study, microcosm plaque biofilms were grown in 24-well microplates on enamel discs for 14 days in artificial saliva. Growth condition comprised cariogenic challenge. The groups (n=10 per group) were: self-ligating brackets (SL); conventional brackets ligated with stainless steel wires (CW); conventional brackets (CE), brackets with hooks (HE), ceramic brackets (KE), and composite brackets (RE), all the four ligated with elastomeric rings. The biofilm formed around the brackets was collected and dry-weighted and the mineral loss around the brackets was determined by cross-sectional microhardness. The third study evaluated in situ the combinated effect of types of brackets and archwire ligation on enamel demineralization, on the accumulation and on microbiological composition of dental plaque. The study design was a modified in situ model, randomized, double-blind and split-mouth. Volunteers (n=17) wore palatal removable appliances containing enamel discs with bonded orthodontic brackets during 14 days. To provide cariogenic challenge, 20% sucrose solution was dripped 8x/day onto each disc. The four conditions under study were: CE; CW; HE; and SL. The biofilm formed around the brackets was collected for microbiological analyses and the mineral loss was determined by cross-sectional microhardness measurement. The systematic review results showed contradictions among studies, and a great methodology variation among them. The reviewed papers did not allow any conclusion about the effect of types of brackets and ligatures on caries lesions and biofilm accumulation. No differences were observed in vitro or in situ regarding biofilm biomass (P>0.05), except for the HE group wich presented lower biofilm accumulation in vitro (P<0.05). Lower demineralization was observed associated to self-ligated brackets, and brackets with more complex design promote higher demineralization than self-ligated brackets. The ligature methods also affected demineralization, and elastomeric rings are more prone to promote caries lesions then steel wires